2021
DOI: 10.1155/2021/6682275
|View full text |Cite
|
Sign up to set email alerts
|

The Distinct Functions of Dopaminergic Receptors on Pain Modulation: A Narrative Review

Abstract: Chronic pain is considered an economic burden on society as it often results in disability, job loss, and early retirement. Opioids are the most common analgesics prescribed for the management of moderate to severe pain. However, chronic exposure to these drugs can result in opioid tolerance and opioid-induced hyperalgesia. On pain modulation strategies, exploiting the multitarget drugs with the ability of the superadditive or synergistic interactions attracts more attention. In the present report, we have rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 118 publications
0
5
2
Order By: Relevance
“…Contrary to our observation, activation of dopamine neurotransmission via D2-like receptors has been shown to relieve pain ( Taylor et al, 2016 ; Liu et al, 2019 ; Wang et al, 2021 ), presumably by inhibiting the excitability of D2-type MSNs in the NAcSh ( Ren et al, 2016 ). For instance, during the acute phase of pain, dopamine neurotransmission via D2-like receptors in the NAc attenuates acute inflammatory pain in rats ( Taylor et al, 2003 ; Dias et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our observation, activation of dopamine neurotransmission via D2-like receptors has been shown to relieve pain ( Taylor et al, 2016 ; Liu et al, 2019 ; Wang et al, 2021 ), presumably by inhibiting the excitability of D2-type MSNs in the NAcSh ( Ren et al, 2016 ). For instance, during the acute phase of pain, dopamine neurotransmission via D2-like receptors in the NAc attenuates acute inflammatory pain in rats ( Taylor et al, 2003 ; Dias et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Augmented phasic dopamine neurotransmission might act as one of the mechanisms underlying the upregulation of D2like receptor function, as activation of D2-like receptors is shown to upregulate the expression of D2-like receptors in the rat striatum (Tokunaga et al, 2012). Contrary to our observation, activation of dopamine neurotransmission via D2-like receptors has been shown to relieve pain (Taylor et al, 2016;Liu et al, 2019;Wang et al, 2021), presumably by inhibiting the excitability of D2-type MSNs in the NAcSh (Ren et al, 2016). For instance, during the acute phase of pain, dopamine neurotransmission via D2-like receptors in the NAc attenuates acute inflammatory pain in rats (Taylor et al, 2003;Dias et al, 2015).…”
Section: Role Of Postsynaptic D2-like Receptors In Immobilization-ind...contrasting
confidence: 70%
“…It has previously been reported that the role of CA1 D2-like dopamine receptors in the acquisition and reinstatement of morphine-induced conditioned place preference was more significant than that of the D1-like dopamine receptors (Assar et al , 2016). It has been postulated that D1-like dopamine receptors in the NAc probably attenuate pain by enhancing the pleasure and reward effects, whereas D2-like dopamine receptors may decrease aversion to pain (Hikida et al , 2013; Wang et al , 2021). According to the present study results, the D1- and D2-like dopamine receptors are involved in the FSS-induced analgesia in the early and late phases of the formalin test.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Importantly, although chlorpromazine is an antagonist/inverse agonist of a series of dopamine, serotonin, and α2 adrenergic receptors, which are expressed in various components of spinal dorsal horn circuitries and supraspinal neurons that send fibres into, and modulate nociceptive processing in, the spinal dorsal horn, it has no analgesic effect in tissue injury. 6 , 9 , 26 , 28 , 88 Therefore, the only plausible explanation for the effect of chlorpromazine on p-S10H3 expression is that, following chlorpromazine injection, the spinal nociceptive input from primary sensory neurons was reduced. That reduction is highly likely because of the inhibitory effect of chlorpromazine on the 18:0 LPC-induced increase in lateral pressure of the cytoplasmic membrane and subsequent activation of TRPV1, TRPV2, and possibly other TRP channels.…”
Section: Discussionmentioning
confidence: 99%